The Investigation of Cooperation Diversity for Communication Exploiting Evaporation Ducts in the South China Sea - Yang, Cheng; Wang, Jian (IEEE transactions on antennas and propagation, 2022)
To improve the communication quality and reliability in the South China Sea (SCS), we proposed a method to exploit the combination of cooperative diversity and evaporation ducts. The simulation results show that the reliability of 300 km ranges at 12 GHz increases from the lowest 43.08% to 94.90% by using space diversity. Communication-link reliability for 100 km ranges may approach 100% or 98% for 200 km ranges. Furthermore, communication effects get significantly improved, and the ratio of signal-to-noise ratio (SNR) exceeds 40 dB that is up to 84.52% with diversity reception. By investigating the cooperation diversity for communication, we could find a favorable condition to realize optional-wide-frequency, long-range, and high-reliability transmission, which supports the scenario of sparse mobile communication in the SCS.